2023
DOI: 10.1093/ibd/izac275
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Effectiveness, and Safety of Ustekinumab for the Treatment of Ulcerative Colitis: A Systematic Review

Abstract: Objective This study aimed to evaluate ustekinumab efficacy, effectiveness, and safety as a treatment for ulcerative colitis in adult patients. Methods A systematic review of the efficacy, effectiveness, and safety of ustekinumab in ulcerative colitis was carried out. The search was conducted via PubMed, Embase, and the Cochrane library. Two reviewers independently assessed the quality of studies and extracted study data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Ustekinumab has a generally favorable safety profile [9, 10, 12-14, 16, 25, 29]. Worsening of UC, nasopharyngitis, and upper respiratory tract infection are the most frequently reported adverse events [10], while discontinuation of the therapy due to adverse events is infrequent [11,13,15,29]. The safety profile of ustekinumab in our study is similar to those reported for the adult population.…”
Section: Discussionsupporting
confidence: 70%
“…Ustekinumab has a generally favorable safety profile [9, 10, 12-14, 16, 25, 29]. Worsening of UC, nasopharyngitis, and upper respiratory tract infection are the most frequently reported adverse events [10], while discontinuation of the therapy due to adverse events is infrequent [11,13,15,29]. The safety profile of ustekinumab in our study is similar to those reported for the adult population.…”
Section: Discussionsupporting
confidence: 70%
“…Overall, although limited by the small sample sizes enrolled and the short follow-up time, these studies provided further reliable evidence for the effectiveness and safety of UST. A systematic review of 13 RW studies [ 89 ] noted that clinical remission and induction were achieved in 24% to 61% and in 47% to 77% of patients, respectively. Moreover, clinical remission was achieved in 33% to 79% of cases at the 52-week follow-up, whereas steroid-free remission was reported in six studies and ranged from 14% to 67%.…”
Section: Resultsmentioning
confidence: 99%
“…In UC, a systematic review of RW data found that patients with AEs ranged from 2.6% to 32% [ 89 ]. In another recent systematic review with a meta-analysis of RW, the incidence rates (iRs) of colectomy, mild and severe AEs, and serious infections were 4.8, 7.9, 0.8, and 0.3 per 100 patient-years, respectively [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has shown the efficacy of ustekinumab, a human IgG1 monoclonal antibody targeting the shared p40 subunit of IL-12/23 for the treatment of CD and UC patients both in randomized clinical trials and real-life experiences [309][310][311][312][313][314][315][316][317]. Ustekinumab is a human IgG1 monoclonal antibody currently approved for the treatment of psoriasis, psoriatic arthritis, and moderate-severe CD and UC [318][319][320]. In a substantial real-world Israeli cohort study involving non-naïve-to-biological-treatment CD patients, ustekinumab demonstrated effectiveness and safety in inducing clinical remission.…”
Section: Il-12/il-23 Inhibitorsmentioning
confidence: 99%